The Wounds That Heal: Heroism and Human Development - Schwartz, Judith A.; Schwartz, Richard E. (Hamilton Books, 2010)
Theories of human development characteristically include a series of stages through which individuals are expected to pass if they are to achieve wholeness and happiness. Whether explicitly or not, such theories privilege 'normalcy.' Heroes, on the other hand, are commonly wounded individuals whose developmental 'disabilities' are ultimately the source of their personal success and heroism. The Wounds that Heal examines developmental theory in the light of the heroic narrative and argues that such theory should be adjusted to accommodate the experience of those who are, in many ways, our principal role models. Four individuals are examined in depth: Jane Austen, T. E. Lawrence, Winston Churchill, and George S. Patton, Jr. The study draws on the experience of a host of other individuals, both historic and fictional, and includes materials designed to aid readers in defining their own views of the heroic as well as to become heroes or heroines in their own lives.